2021
DOI: 10.1002/gps.5501
|View full text |Cite
|
Sign up to set email alerts
|

Neural links between facial emotion recognition and cognitive impairment in presbycusis

Abstract: Objectives Facial emotion recognition (FER) is impaired in people with dementia and with severe to profound hearing loss, probably reflecting common neural changes. Here, we aim to study the association between brain structures and FER impairment in mild to moderate age‐related hearing loss participants. Methods We evaluated FER in a cross‐sectional cohort of 111 Chilean nondemented elderly participants. They were assessed for FER in seven different categories using 35 facial stimuli. We collected pure‐tone av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
(83 reference statements)
0
15
0
Order By: Relevance
“…A future experimental protocol should include dynamic material, both visual (colorized) and auditory, such as videos, to confirm our results. There is a correlation between hearing loss and FER impairment due to superior temporal sulcus atrophy, which is a key region for FER (Gobbini and Haxby, 2007), following presbycusis (Belkhiria et al, 2021). Although none of the individuals in our study had significant hearing loss, we did not conduct an audiologic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A future experimental protocol should include dynamic material, both visual (colorized) and auditory, such as videos, to confirm our results. There is a correlation between hearing loss and FER impairment due to superior temporal sulcus atrophy, which is a key region for FER (Gobbini and Haxby, 2007), following presbycusis (Belkhiria et al, 2021). Although none of the individuals in our study had significant hearing loss, we did not conduct an audiologic assessment.…”
Section: Discussionmentioning
confidence: 99%
“… Belkhiria et al ( 66 ) controlled for education, cognitive abilities, visuospatial capacities, (neuro-) psychiatric symptoms. Belkhiria et al ( 24 ) controlled for education, cognitive abilities, dementia, smoking, cardiovascular risk factors, diabetes, depression.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, it was unclear whether confounding variables were controlled for in analyses, but the two groups (ARHL and no-ARHL) were matched for age, sex, and education, and showed statistically similar cognitive functioning across a range of tests ( 64 ). Critically, the four remaining studies state explicitly that statistical analyses accounted for both age and sex ( 22 , 24 , 65 , 66 ). Further, three studies controlled for education ( 24 , 65 , 66 ), and three controlled for total estimated intracranial volume ( 22 , 24 , 65 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OAE and ABR also have the potential to determine which ARHL patients could be at risk of having a cognitive impairment (Belkhiria et al, 2019 , 2020 ; Delano et al, 2020 ). In addition, a recent study found that impaired facial emotion recognition in ARHL patients is correlated with the atrophy of multiple areas of the cerebral cortex and may also relate to cognitive impairment (Belkhiria et al, 2021 ). Future research may find more reliable biomarkers for cognitive decline caused by ARHL.…”
Section: Discussionmentioning
confidence: 99%